Pengaruh cyberloafing, stres kerja, dan komitmen organisasional terhadap niat untuk berpindah kerja pada karyawan generasi z di Jakarta Selatan - Suwandi, Daffa Harits; Levianto, Jubei; Fathoni, Muhammad Anwar (Universitas Widya Mataram, 2025)
This study aims to analyze the influence of cyberloafing, job stress, and organizational commitment on turnover among Generation Z employees in South Jakarta. The phenomenon of high turnover rates of young employees in the digital era is a significant issue that requires special attention in human resource management. This study uses a quantitative approach with a survey method by distributing structured questionnaires to Generation Z employees selected using a purposive sampling technique. The data obtained were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) to test the direct influence between variables. The results show that cyberloafing and job stress have a positive and significant effect on turnover, while organizational commitment has a negative and significant effect, thus reducing turnover intentions among Generation Z. These findings provide a theoretical contribution by expanding the study of turnover models in the Generation Z group, which is still limited in the context of developing markets. Practically, the results of this study can be a basis for organizations to reduce cyberloafing behavior, reduce job stress, and increase organizational commitment through appropriate digital policies, training, and career development